2015
DOI: 10.4187/respcare.03565
|View full text |Cite
|
Sign up to set email alerts
|

Response of Preterm Infants to 2 Noninvasive Ventilatory Support Systems: Nasal CPAP and Nasal Intermittent Positive-Pressure Ventilation

Abstract: BACKGROUND: Noninvasive ventilation (NIV) in preterm infants is currently applied using intermittent positive pressure (2 positive-pressure levels) or in a conventional manner (one pressure level). However, there are no studies in the literature comparing the chances of failure of these NIV methods. The aim of this study was to evaluate the occurrence of failure of 2 noninvasive ventilatory support systems in preterm neonates over a period of 48 h. METHODS: A randomized, prospective, clinical study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
14
0
3
Order By: Relevance
“…A total of 8418 studies were identified through searching the different databases. After excluding studies for relevant reasons, a total of 33 studies were included in the final synthesis 21‐53 . The literature search flow is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8418 studies were identified through searching the different databases. After excluding studies for relevant reasons, a total of 33 studies were included in the final synthesis 21‐53 . The literature search flow is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were adjudged as having a high risk of bias due to issues in random sequence generation and allocation concealment 30,32,33,39,40,43‐45,47,53 . Eight studies had a low risk of bias 21,23,25,26,42,48,50,52 and fifteen studies had variable risk of bias 22,24,27‐29,31,34‐38,41,46,49,51 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIMV compared to NCPAP as initial treatment for RDS in preterm newborns of < 35 weeks of gestation demonstrated decreased need for intubation and decreased BPD rate with NIMV [29]. Silveira et al [30] found that for preterm infants of gestational age < 37 weeks and birth weight < 2500 g, failure on NIPPV support compared to CPAP was less likely and the rate of intubation was higher when using CPAP. Moreover, occurrence of apnea episodes was lower in the NIPPV group.…”
Section: Comparisonmentioning
confidence: 99%
“…44-53 In the updated search, we identified 6 new eligible studies. 54-58 These form the basis of this review.…”
Section: Questions Evidence Summary and Recommendationsmentioning
confidence: 99%